Adaptive Load Balancing Techniques for Improved Cloud Service Performance - Sangle Harshal Sunil; Jeetendra Singh Yadav (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Cloud computing has emerged as a fundamental platform for delivering scalable, flexible, and cost-effective computing services. However, the rapid growth of users and heterogeneous workloads often leads to challenges such as uneven resource utilization, performance degradation, and service-level agreement (SLA) violations. Load balancing plays a crucial role in overcoming these issues by efficiently distributing incoming workloads across multiple servers to optimize resource usage, minimize response time, and ensure system reliability. This paper focuses on adaptive load balancing techniques that dynamically adjust to fluctuating workloads and varying system conditions, unlike traditional static approaches. By leveraging machine learning algorithms, heuristic models, and feedback-driven optimization strategies, adaptive techniques enable real-time decision-making for efficient task allocation. The study highlights key methods, including predictive workload analysis, adaptive VM migration, and hybrid balancing algorithms, that improve system throughput, reduce latency, and enhance overall cloud service performance. The findings demonstrate that adaptive load balancing is essential for achieving high availability, fault tolerance, and sustainable cloud operations, making it a promising approach for next-generation cloud infrastructures.